2020
DOI: 10.3389/fcimb.2020.00274
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Genetic Characteristics of Resistance and Virulence of the “Epidermidis Cluster Group” Through Pan-Genome Analysis

Abstract: Staphylococcus caprae, Staphylococcus capitis, and Staphylococcus epidermidis belong to the "Epidermidis Cluster Group" (ECG) and are generally opportunistic pathogens. In this work, whole genome sequencing, molecular cloning and pan-genome analysis were performed to investigate the genetic characteristics of the resistance, virulence and genome structures of 69 ECG strains, including a clinical isolate (S. caprae SY333) obtained in this work. Two resistance genes (blaZ and aadD2) encoded on the plasmids pSY33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 71 publications
(82 reference statements)
3
14
0
Order By: Relevance
“…We display for the first time that S. sciuri has an open pan-genome, with an ever-increasing flexible genome as new strains are added. Similar patterns were observed in other clinically relevant staphylococcal species formerly analyzed, such as S. aureus ( 50 ), S. epidermidis ( 51 53 ), Staphylococcus haemolyticus ( 54 ), Staphylococcus capitis , and Staphylococcus caprae ( 52 ). This result could be anticipated, as an open pan-genome is characteristic of species living in multiple environments and/or mixed bacterial communities.…”
Section: Discussionsupporting
confidence: 79%
“…We display for the first time that S. sciuri has an open pan-genome, with an ever-increasing flexible genome as new strains are added. Similar patterns were observed in other clinically relevant staphylococcal species formerly analyzed, such as S. aureus ( 50 ), S. epidermidis ( 51 53 ), Staphylococcus haemolyticus ( 54 ), Staphylococcus capitis , and Staphylococcus caprae ( 52 ). This result could be anticipated, as an open pan-genome is characteristic of species living in multiple environments and/or mixed bacterial communities.…”
Section: Discussionsupporting
confidence: 79%
“…We also found the Ser-Asp-rich proteins sdrE to be enriched in ocular-sourced strains (16/17) compared to blood-sourced strains (24/46) (Fisher' exact test, FDR < 0.05). Two toxin genes, sell and sec, which were present in only two strains of blood-sourced S. epidermidis (SE90 and SE95), as reported previously (68), were also identified in two ocular strains, combining the results of phylogenetics showing that the strains had a close evolutionary distance, implying that they may have the similar founder lineages.…”
Section: S Epidermidis Containssupporting
confidence: 70%
“…We also found that the sdrE gene encoding the Ser-Asp-rich protein was enriched in ocular-sourced strains (16/17) compared to blood-sourced strains (24/46; Fisher's exact test, FDR < 0.05). Two toxin genes, sell and sec, which were present only in two S. epidermidis strains isolated from blood (SE90 and SE95), which reported previously (Sun et al, 2020), were also identified in two ocular strains. Together with the results from phylogenetic analysis showing that these strains had a close evolutionary distance, implying that they may have the similar founder lineages.…”
Section: The Virulence Characteristics Of Staphylococcus Epidermidissupporting
confidence: 57%